Lectin‐Like Oxidized Low‐Density Lipoprotein Receptor 1 Inhibition in Type 2 Diabetes: Phase 1 Results - Andrea L. Vavere; Marvin Sinsakul; Emily L. Ongstad; Ye Yang; Vijayalakshmi Varma; Christopher Jones; Joanne Goodman; Vincent F. S. Dubois; Angelica L. Quartino; Sotirios K. Karathanasis; Liron Abuhatzira; Anna Collén; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Blockade of the lectin‐like oxidized low‐density lipoprotein receptor‐1 (LOX‐1) is a potentially attractive mechanism for lowering inflammatory and lipid risk in patients with atherosclerosis. This study aims to assess the safety, tolerability, and target engagement of MEDI6570, a high‐affinity monoclonal blocking antibody to LOX‐1. Methods and Results This phase 1, first‐in‐human, placebo‐controlled study (NCT03654313) randomized 88 patients with type 2 diabetes to receive single ascending doses (10, 30, 90, 250, or 500 mg) or multiple ascending doses (90, 150, or 250 mg once monthly for 3 months) of MEDI6570 or placebo. Primary end point was safety; secondary and exploratory end points included pharmacokinetics, immunogenicity, free soluble LOX‐1 levels, and change in coronary plaque volume. Mean age was 57.6/58.1 years in the single ascending doses/multiple ascending doses groups, 31.3%/62.5% were female, and mean type 2 diabetes duration was 9.7/8.7 years. Incidence of adverse events was similar among cohorts. MEDI6570 exhibited nonlinear pharmacokinetics, with terminal half‐life increasing from 4.6 days (30 mg) to 11.2 days (500 mg), consistent with target‐mediated drug disposition. Dose‐dependent reductions in mean soluble LOX‐1 levels from baseline were observed (>66% at 4 weeks and 71.61–82.96% at 10 weeks in the single ascending doses and multiple ascending doses groups, respectively). After 3 doses, MEDI6570 was associated with nonsignificant regression of noncalcified plaque volume versus placebo (−13.45 mm3 versus −8.25 mm3). Conclusions MEDI6570 was well tolerated and demonstrated dose‐dependent soluble LOX‐1 suppression and a pharmacokinetic profile consistent with once‐monthly dosing. Registration URL: https://clinicaltrials.gov/; Unique identifier: NCT03654313.